Tophi which develop years before the first attack of acute gouty arthritis - Hidayat, Rudy; Kasjmir, Yoga I (Indonesian Rheumatology Association, 2009)
Gout is a clinical disease associated with hyperuricemia and caused by the deposition ofmonosodium urate crystals in and around the tissue of joints. The course of classic gout passes through three distinct stages: asymptomatic hyperuricemia, acute intermittent gout, and advanced gout/chronic tophaceous gout.1,2 Tophi; described as accumulation of articular, osseus, soft tissue, and cartilaginous crystalline deposits; is one of clinical manifestation of chronic tophaceous gout stage, and usually developedafter 10 or more years of acute intermittent gout.1,2 Although patients have been reported with tophias their initial clinical manifestation